PENERAPAN MODEL EXPERIENTAL LEARNING MELALUI METODE DISKUSI PADA MATERI PENGELOLAAN KEUANGAN SEDERHANA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XII MANAJEMEN PERKANTORAN1 SMK NEGERI 1 TASIKMALAYA - Suprapti, Tati (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
The problem in this research is whether the application of the Experiential Learning Model through the Discussion Method can improve the learning outcomes of class XII MP1 students at SMK Negeri 1 Tasikmaya. The aim of the research is to increase the effectiveness of implementing the Experiential Learning Model through the Discussion Method in an effort to improve learning outcomes for Simple Financial Management Material. Perpetual Assessment Method for class The subjects in this research were 35 students of Class XII Office Management1 at SMK Negeri 1 Tasikmalaya for the 2022/2023 academic year. Student learning effectiveness is measured based on individual learning completeness criteria. The results of the research show that through the application of the Experiential Learning Model through the Discussion Method it can increase student activity and competence in simple Financial Management subjects. . This can be seen from: (1) there is an increase in student activity in each cycle. Student activity in cycle I was 37.13%, and cycle II was 76.16%; (2) there is an increase in class averages and student learning completeness. The class average in cycle I was 80 and cycle II was 87. Student learning completeness as measured by the cognitive competency test in cycle I was 66%, and cycle II was 91.62%. The conclusion from the research results regarding the Application of the Experiential Learning Model Through the Discussion Method in Class XII Office Management 1 SMK Negeri 1 Tasikmalaya was declared successful